IMPROVING STUDENTS’ SPEAKING COMPETENCE BY USING ROLE PLAY (A CLASSROOM ACTION RESEARCH ON THE EIGHTH GRADE STUDENTS IN THE A CLASS AT SMP NEGERI 1 BANJAR) - ., I Made Ery Indrawan; ., Drs. Asril Marjohan,MA; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan siswa menggunakan teknik role play. Subjek penelitian ini adalah siswa kelas delapan kelas A di SMP Negeri 1 Banjar, tahun akademik 2015/2016. Jumlah subjek penelitian ini adalah 37 siswa. Penelitian ini di desain menggunakan penelitian tindakan kelas dimana dilakukan dalam dua siklus. Tiap siklus berisi empat langkah seperti: perencanaan, tindakan, observasi, dan refleksi. Pre-test diberikan kepada siswa untuk mengetahui pengetahuan dasar pada kosa kata yang telah mereka pelajari. Data diperoleh dengan menggunakan dua jenis instrument: test dan questionnaire yang di analisis secara deskirptif. Hasil penelitian ini menunjukkan bahwa role play dapat efektif meningkatkan kemampuan siswa di berbicara. Peningkatan siswa di lihat dari skor rata-rata yang diperoleh siswa. Skor rata-rata pre-test adalah 51,13 dan ini dalam tingkat kurang. Peningkatan Skor menjadi 66,32 di posttest 1 yang mana berada di tingkat baik. Peningkatan skor menjadi 70,05 berada di tingkat baik. Hasil dari questionnaire dan informal interview mengindikasikan bahwa 85,83% siswa menyukai pelajaran bahasa Inggris dengan menggunakan teknik role play dengan motivasi tinggi. Dapat disimpulkan bahwa role play adalah teknik yang efektif untuk meningkatkan kemampuan siswa dalam berbicara bahasa Inggris Kata Kunci : Berbicara, teknik role play This study was aimed at improving speaking competence of the students by using role play technique. The subjects of this research were the eighth grade students of class A at SMP Negeri 1 Banjar in the academic year 2015/2016. The total number of subjects was 37 students. This study was designed with a classroom action research which was conducted in two cycles that consisted of four meetings, three meetings were used to apply the role play technique and one meeting was used for the test and questionnaire. Each cycle involved four steps namely: planning, action, observation, and reflection. Pre-test was given to students in order to know the initial knowledge on vocabulary they had learnt. The data were obtained using two kinds of instruments: tests and questionnaires that would be analyzed descriptively. The result of this study showed that role play could effectively improve the students’ competence in speaking. The improvement of the students was noted from the mean score obtained by the students. The mean score of the pre test was 51.13 and this was in poor level. The score increased up to 66.32 in post test 1 in which was good level. The score increased up to 70.05 and was a good level. The result of questionnaire indicated that 85.83% and 98.91% students liked learning English by using role play technique with high motivation. It can be concluded that role play was effective technique to improve students’ competence in speaking Englishkeyword : speaking, role play technique